Identify and built a control of systems with backlash - Nguyen, Duy Anh; Phung, Vũ Lâm (Journal of Technical Education Science, 2015)
This paper addresses one non-differentiable non-linearity which usually appears in industrial mechanism: backlash. We introduce an algorithm including backlash-inverse function and MRAs (Model reference adaptive system) to identify and control a black-box system (including a transfer function, a backlash function and disturbances). The effect of the algorithm provided is verified in theoretical simulation and in the experiment